2022
DOI: 10.12998/wjcc.v10.i31.11590
|View full text |Cite
|
Sign up to set email alerts
|

Primary hepatic angiosarcoma: A case report

Abstract: BACKGROUND Primary hepatic angiosarcoma (PHA) is a rare malignant tumor of the vascular endothelium. Clinical manifestations and laboratory and imaging examinations often lack specificity for PHA. We report a case of PHA, and describe the ultrasound characteristics and characteristic changes in laboratory values associated with PHA. CASE SUMMARY A 75-year-old woman presented with right upper quadrant abdominal pain for half a month. Magnetic resonance imaging (MRI) at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Both HS HSC are rare tumor with high malignancy and poor prognosis [1,5,11] In our study, we did not nd any signi cant difference between the two tumors in the tumor markers, such as AFP, CEA and CA1-99. This is consistent with previous ndings that tumor markers are non-speci c [11,12,14] .Meanwhile, we found signi cant differences between the hepatitis and cirrhotic backgrounds of the two tumor. In our study, 11 patients with HSC had 6 cases of hepatitis (54.5%) and 6 cases of cirrhosis (54.5%), while 12 patients with HS had 0 cases of hepatitis (0%) and 1 case of cirrhosis (8.3%).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Both HS HSC are rare tumor with high malignancy and poor prognosis [1,5,11] In our study, we did not nd any signi cant difference between the two tumors in the tumor markers, such as AFP, CEA and CA1-99. This is consistent with previous ndings that tumor markers are non-speci c [11,12,14] .Meanwhile, we found signi cant differences between the hepatitis and cirrhotic backgrounds of the two tumor. In our study, 11 patients with HSC had 6 cases of hepatitis (54.5%) and 6 cases of cirrhosis (54.5%), while 12 patients with HS had 0 cases of hepatitis (0%) and 1 case of cirrhosis (8.3%).…”
Section: Discussionsupporting
confidence: 93%
“…They are unusual, featured with nonspeci c symptoms, and often present asymptomatic until they have become large, leading to a clinical dilemma. Clinically, asymptomatic, epigastric pain, bloating, anorexia, fatigue and weight loss are main symptoms of these two liver tumors [11][12][13][14] . It has been reported that HSC and HS are initially misdiagnosed as hepatic abscess, HCC, and malignant tumor (MT) by imaging [15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%